High contribution of methane in greenhouse gas emissions from a eutrophic lake: a mass balance synthesis - Arianto B. Santoso; David P. Hamilton; Louis A. Schipper; Ilia S. Ostrovsky; Chris H. Hendy (New Zealand Journal of Marine and Freshwater Research, 2021)
Lakes are ‘hotspots’ for greenhouse gas (GHG) emissions, primarily carbon dioxide (CO 2 ) and methane (CH 4 ). Understanding the processes regulating GHG emissions from lakes, and their temporal variability, is essential for more accurately quantifying the role of lakes in global GHG cycles. In this study, we identified the processes that affect CO 2 and CH 4 concentrations in a small (0.3 km 2 ) eutrophic monomictic lake (Okaro, New Zealand). A mass balance model was used to calculate changes in CO 2 and CH 4 storage in the lake as a result of internal cycling and atmospheric fluxes. To support model computations, CO 2 and CH 4 concentrations profiles were measured monthly over a one‐year period, in addition to temperature, dissolved oxygen and chlorophyll a . Annually, Lake Okaro acted as a sink of CO 2 from the atmosphere (425.4 mmol CO 2 m −2 y −1 ) and a source of CH 4 (553.4 mmol CH 4 m −2 y −1 ) equating to a net GHG emission (diffusive fluxes of CO 2 and CH 4 combined) of 0.22 kg CO 2 ‐eq m −2 y −1 . Although it may be viewed as conservative and applies only to diffusive fluxes, our study indicates that eutrophic lakes with high rates of primary production may act as a net source of GHGs.